The Use of Color T2 Mapping in MRI Examination of Children with Recurrent Patellar Dislocations in the Postoperative Period - Evgeniy A. Andronnikov; Tatiana V. Alekseeva; Natalia G. Mikhalkina; Ayrat R. Syundyukov; Elena V. Preobrazhenskaya (Вестник рентгенологии и радиологии)
Background. Patellar instability in childhood and adolescence may be associated with a violation of its tracking, which often leads to the development of recurrent dislocation and rapid progression of degenerative-dystrophic changes in cartilage tissue. The standard protocol of magnetic resonance imaging (MRI) at the initial biochemical stages of cartilage matrix transformation is not effective enough to assess the shape of the patella, the degree of facet development, the state of articular cartilage, and the integrity of the supporting ligaments of the patella. Quantitative relaxation time T2 during cartilage MR mapping is a noninvasive marker of cartilage degeneration, sensitive to biochemical composition and degree of tissue hydration. T2 mapping can complement the study due to its high diagnostic significance in the early stages of arthrosis development.Objective: to assess the condition of patellar articular cartilage after stabilizing arthroscopic surgery for recurrent patellar dislocation in children using MRI with color T2 mapping.Material and methods. The study included 22 adolescents aged 15–17 years (13 boys, 9 girls) with habitual patellar dislocation. All patients underwent stabilizing surgical treatment. Before the operation, clinical tests, X-ray examinations in three projections, ultrasound and computed tomography of knee joints were performed. Knee joint MRI before, on day 3 and 6 months after surgery was supplemented with color mapping of patellar cartilage tissue with calculation of T2 relaxation time.Results. Local areas in the loaded areas of patellar cartilage with an average T2 relaxation time of 35.5 ms before surgery were detected in all patients. On day 3, with the correct position of the patella, the T2 relaxation time increased to 37.8 ms. After 6 months, 86.4% of patients showed a decrease, including in 73.7% of cases – up to 28.6 ms on average.Conclusion. MRI with color T2 mapping makes it possible to assess the restoration of cartilage structure after stabilizing surgical treatment. A slowdown in the processes of chondro-degeneration and a regenerative effect are noted as early as 6 months after surgery.